Effects of footwear with different longitudinal bending stiffness on biomechanical characteristics and muscular mechanics of lower limbs in adolescent runners - Chen, Hairong; Shao, Enze; Sun, Dong; Xuan, Rongrong; Baker, Julien S.; Gu, Yaodong (Frontiers in Physiology, 2022)
Background: For Carbon plate running shoes have been proven to improve sports performance from a biomechanical perspective. However, the effects of the different longitudinal bending stiffness of footwear on lower limb biomechanics and muscle mechanics of adolescent runners are still unclear. The purpose of this study was to investigate differences in the running stance phase of teenage runners wearing low longitudinal bending stiffness (Llbs) and high longitudinal bending stiffness (Hlbs) running shoes. Methods: We recruited 10 male adolescent runners involved in regular running training (age: 13.5±0.6 years; height: 166.3±1.9cm; weight: 50.8±3.1kg; foot length: 25.4±0.2cm). Subjects were asked to wear running shoes of two stiffnesses for the running task. Paired samples t-test and statistical parametric mapping (SPM) analysis were used to investigate any differences between different stiffness shoes during the running stance phases. Result: Contact time of Hlbs showed significant increases (p=0.003); the angle range of motion (ROM) of Hlbs showed significant decreases in the hip sagittal plane (p=0.001) and mpj sagittal plane (p=0.001) compared to the Llbs; the peak moment of Hlbs showed significant decreases in knee sagittal plane (p=0.023) and ankle sagittal plane (p=0.023) compared to the Llbs; the peak muscle force of Hlbs showed significant decreases in rectus femoris (p=0.026), vastus medialis (p=0.042) and flex hall long (p=0.012); the force-time of Hlbs showed significant decreases in gluteus max2 (p=0.011), significant increases in vastus medialis(p=0.001), vastus lateralis (p=0.001), medial gastrocnemius (p=0.005), lateral gastrocnemius (p=0.007), flex dig brevis (p=0.001), flex hall long (p=0.001) and tibialis anterior (p=0.040). During the running stance phase, the angles and moments of the hip, knee, ankle, and metatarsophalangeal joints were different under different bending stiffness conditions; the muscle force of gluteus max2, rectus femoris, vastus medialis, vastus lateralis, medial gastrocnemius and tibialis anterior were different under different bending stiffness conditions. Conclusion: Due to musculoskeletal developmental characteristics, adolescent runners are more suitable for shoes with lower longitudinal bending stiffness.